Improving the readiness of teachers for using distance technologies in supplementary technical education: A case study in Kazakhstan - Shumeiko, Tatyana; Bezhina, Viktoriya; Zhiyenbayeva, Aida; Bozhevolnaya, Nataliya; Zubko, Nataliya (International Journal of Innovative Research and Scientific Studies, 2024)
The pandemic-induced shift to distance learning brought significant changes to supplementary education, impacting content representation, teaching methods, assessment, and digital interaction. The purpose of the study was to investigate the readiness of supplementary technical education teachers in Kazakhstan to employ distance technologies in developing schoolchildren’s technical creativity during and after the pandemic. Furthermore, the study aimed to implement a professional development program to enhance teachers’ preparedness. To achieve the goal of the study, the authors used theoretical analysis to assess teachers’ readiness for distance technologies. When developing a professional program, the modeling method was used. Empirical methods, including student portfolios, curriculum assessment through peer review, and semi-structured interviews, were conducted in four regions of Kazakhstan in 2022-2023 with the participation of 30 technical education teachers. Results indicate that teachers with varying levels of experience initially exhibited differences in motivational, content-based, and procedural readiness. However, the Moodle program positively influenced these aspects for both groups. This study offered insights into the transformation of teacher readiness in supplementary technical education amidst evolving educational landscapes. The recommendations and outcomes can be applied to the systems of supplementary technical education for children in terms of organization, analysis, and sustainability of approaches to the creation of digital content.